HUBUNGAN TINGKAT PENGETAHUAN MENSTRUASI DENGAN KESIAPAN MENARKHE SISWI SD KELAS 4, 5, DAN 6 - Rhomawati, Wahyu Surya; Estiwidani, Dwiana; Wahyuningsih, Heni Puji (Poltekkes Kemenkes Yogyakarta, 2014)
Indonesian population dominated by adolescent age group (10-19 years) of approximately 18%. State   population dominated adolescence because teenagers pose new problems including the age group that needs special attention, especially In the reproduction rights. Lack of knowledge on adolescent girls about menstruation in particular reproduction is likely to have an impact on the attitude of facing menarkhe.The purpose to determine the relationship of the level of knowledge of menstruation with readinessmenarkhe elementary school grades 4, 5, and 6 at SDUnggaran 1Yogyakarta 2014. This research is an analytical surveycorrelational cross-sectional approach. The study was conducted in SD Unggaran 1 Yogyakarta on March 27, 2014 subjects were elementary school classes 4,5, and 6 age 10-12 years who have not been menstruating by 43 respondents. Data collection instruments such as questionnaires. Data were analyzed usingChi Square. The results showed the highest level of knowledge is at the level quite as many as 19 (44.2%)respondents. On respondents knowledgeable enough knowledge obtained 10(52.6%) respondents are ready to face and onthelevel of knowledgemenarkhe less. The bivariate analysis usingChi Square test ISMSPSS 20 computer programwith a 95%confidence level is obtained X2 count of 8,05. The amount is greater than the X2 table at df-3-1:1 (2), with a significance level of 0,05, which is worth 5,591. This means that the count X2> X2 table is 8,05>5,59. In addition, the results obtained also that the p-value is 0,01 or ? count. This suggests that the ? count<? of 0.01 <0.05. In conclusion there is a correlation with the level of knowledge menstrual menarkhe elementary school readiness classes 4, 5, and 6 at SD Unggaran 1 Yogyakarta in 2014.